2016
DOI: 10.1002/2016je005010
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of Martian glass analogues: A tool to approximate their chemical composition

Abstract: Raman spectrometers will form a key component of the analytical suite of future planetary rovers intended to investigate geological processes on Mars. In order to expand the applicability of these spectrometers and use them as analytical tools for the investigation of silicate glasses, a database correlating Raman spectra to glass composition is crucial. Here we investigate the effect of the chemical composition of reduced silicate glasses on their Raman spectra. A range of compositions was generated in a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 53 publications
(110 reference statements)
2
32
0
Order By: Relevance
“…Typically, a predictive model is created using measurements of standard materials with known concentrations, which can then be used to predict the concentration of unknown materials. Many statistical methods, or combinations of methods, have been proposed for data generated by various LIBS instruments, see previous studies . However, it is uncertain which analytical procedure should be accepted as a standard methodology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, a predictive model is created using measurements of standard materials with known concentrations, which can then be used to predict the concentration of unknown materials. Many statistical methods, or combinations of methods, have been proposed for data generated by various LIBS instruments, see previous studies . However, it is uncertain which analytical procedure should be accepted as a standard methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Many statistical methods, or combinations of methods, have been proposed for data generated by various LIBS instruments, see previous studies. [10][11][12][13][14][15][16] However, it is uncertain which analytical procedure should be accepted as a standard methodology. Principal component analysis (PCA), for example, has been a particularly popular method given its success in data visualization and pattern recognition on a lower-dimensional scale 17 ; however, its efficacy in LIBS data will vary from application to application and between instruments.…”
mentioning
confidence: 99%
“…Empirical vibrational assignments to the Raman spectral features of these glasses have been frequently determined through comparisons between features in the spectra of the silicate glasses and in those of crystals with similar chemical compositions[e.g., Brawer and White , , ; Etchepare , ; McKeown et al ., ; McMillan et al ., ; Williams et al ., ] or based on vibrational calculations for molecular clusters within the glasses [e.g., Brawer and White , , ; Furukawa et al ., ; Marinov et al ., ; Zotov et al ., , ]. In recent years, Raman spectroscopy has been developed as a quantitative method of determining ferric iron concentration in glasses [ Baert et al ., ; Magnien et al ., ; Di Muro et al ., ; Di Genova et al ., ], the water contents in silicate glasses and minerals [ Thomas , ; Arredondo and Rossman , ; Zajacz et al ., ; Behrens et al ., ; Di Muro et al ., ; Thomas et al ., ], and the chemical compositions of silicate glasses [e.g., Di Genova et al ., , ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors [16,29,33,[36][37][38], investigating the effect of iron on the vibrational response of glasses, demonstrated that both iron content and its redox state strongly influence the Raman spectra. These authors showed that the ratio Fe 3+ /Fe tot could be calculated by using different treatments of the spectra involving baseline fitting and/or deconvolution in Gaussian components associated to Q n -species (Q n distinguishes silicon atoms according to the number n of coordinated bridging oxygens (BO), i.e., Q 4 stands for silicon coordinated by four BO, Q 3 corresponds to three BO and one nonbridging oxygen (NBO), etc.)…”
Section: Estimating Composition and Redox State Of Silicate Glasses Amentioning
confidence: 99%
“…The HW envelope is the most sensitive to changes of redox conditions and is commonly deconvoluted in order to quantify the effect of iron oxidation state [16,33]. The investigation of vibration in the HW region has also the advantage of avoiding the contributions potentially provided by the presence of nanolites of oxide crystals (e.g., 16,77) and for the same reason is frequently used for studies devoted to characterize the effect of oxidation state of iron in basaltic to pantelleritic compositions [14,16,33,38,76,77]. Table A1 reports a summary of the main kind of vibration frequencies for some of the most well-known alumino-silicate and iron-bearing alumino-silicate melts.…”
Section: Appendix A2 Lw Mw and Hw Bands In Silicate Melts And Glassesmentioning
confidence: 99%